Energy transport through Earth’s plasma sheet in 3-D - Barik, K. C.; Chaston, C. C. (Frontiers in Astronomy and Space Sciences, 2025)
A statistical analysis of energy transport through Earth’s plasma sheet is performed using 6 years of Magnetospheric Multi-Scale (MMS) mission observations. The analysis entails a complete decomposition of the contributions to transport including the ion heat flux and enthalpy flux derived from the full ion pressure tensor to provide a three-dimensional (3-D) picture of plasma sheet energy transport. It is shown that the Poynting flux and enthalpy flux compete to dominate the total energy transport, while the heretofore ignored heat flux generally contributes a larger fraction of the total energy flux than the bulk kinetic energy flux. The spatial distribution of these fluxes are consistent with magnetic reconnection driven transport from an X-line statistically located at X∼−20RE. Kinetic fluxes stream Earthward from this point peaking mid-tail along the neutral sheet, while Poynting fluxes peak at higher latitudes and along the inner edge of the plasma sheet.